Efficient Inactivation of Monkeypox Virus by World Health Organization‒Recommended Hand Rub Formulations and Alcohols - Toni L. Meister; Ronny Tao; Yannick Brüggemann; Daniel Todt; Joerg Steinmann; Joerg Timm; Ingo Drexler; Eike Steinmann (Emerging Infectious Diseases, 2023)
Increasing nonzoonotic human monkeypox virus (MPXV) infections urge reevaluation of inactivation strategies. We demonstrate efficient inactivation of MPXV by 2 World Health Organization‒recommended alcohol-based hand rub solutions. When compared with other (re)emerging enveloped viruses, MPXV displayed the greatest stability. Our results support rigorous adherence to use of alcohol-based disinfectants.